Hubungan Stres Kerja dengan Kinerja Perawat Terhadap Proses Asuhan Keperawatan di Unit Rawat Inap RSUD Khidmat Sehat Afiat Kota Depok tahun 2022: Stres Kerja dengan Kinerja Kerja - Maulida Khalizahy; Azizah Zen; Fini Fajrini (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Work Stress is a condition in which a person feels obstacles or demands related to what is expected and considered to be successful but not as expected. Increased work stress causes nurse must role in a manner maximum in serves patients, some symptom consequence stress includes laziness, experiencing change lust eating, and often sick head. So that could affect the performance of nurses. This research uses a cross-sectional research design. The sample used the total sampling method with a total sample of 69 respondents. The analysis was performed using the chi-square test. From 69 respondents work stress with the performance of nurses in the inpatient unit of Khidmat Sehat Afiat Hospital, Depok City, in the moderate stress level category there were 44 nurses with a percentage of 63.8% with poor nurse performance as many as 25 nurses with a percentage of 56.8% and nurses with good performance as many as 19 nurses with a percentage of 43.2%. The results of the Chi-square statistical test with Crostabulation using α = 0.05 found a p-value of 0.026, so it can be concluded that the p-value <α = 0.05, which means that there is a significant relationship between work stress and nurse performance. There is a Connection Between stress Work with Nurse Performance, listening indicator psychology, physical, and behavior as indicator measurement of work stress. Home it hurts more to notice condition stress nurse with given a chance to develop a career and education, as well as analyze the burden work nurse.